ANALISA SEMIOTIKA FERDINAND DE SAUSSURE TERHADAP LIRIK LAGU “SAKURA NO HANABIRATACHI” KARYA JKT48 - Fahmi Handiansyah; Muhammad Rizki Fadhillah, Calvin Eka Sambora, Zaky Aulia Drajat, Riza Fahlapi (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This study aims to interpret the meaning of farewell contained in the lyrics of the song "Sakura No Hanabiratachi" by JKT48 using Saussure's semiotic theory. The research method used is literature study with qualitative-descriptive data analysis technique. The results of the analysis indicate that the lyrics depict feelings of nostalgia, sadness, and optimism in facing farewells and changes in life. The lyrics utilize metaphors and natural imagery to convey messages about the beauty and complexity of life, the importance of hope, courage, and support in facing challenges, and the value of memories and personal growth